Complications of Pregnancy and the Risk of Developing Endometrial or Ovarian Cancer: A Case-Control Study - Liu, Yang; Chen, Xingyu; Sheng, Jiayi; Sun, Xinyi; Chen, George Qiaoqi; Zhao, Min; Chen, Qi (Frontiers in Endocrinology, 2021)
Background The association of complications of pregnancy and the risk of developing gynecological cancer is controversial with the limited study. In this study, we investigated the association of preeclampsia, or gestational diabetes mellitus (GDM), or large for gestational age (LGA), or intrauterine growth restriction (IUGR) and the risk of endometrial or ovarian cancer. Methods In this case-control study, 189 women with endometrial cancer and 119 women with ovarian cancer were included. 342 women without gynecological cancers were randomly selected as a control group. Data on the history of pregnancy and age at diagnosis of gynecological cancer as well as the use of intrauterine devices (IUDs) were collected. Results Women with a history of preeclampsia or IUGR did not have an increased risk of developing endometrial or ovarian cancer. While women with a history of GDM or with the delivery of LGA infant increased the risk of developing endometrial cancer but not ovarian cancer. The odds of women with a history of GDM or with the delivery of LGA infant developing endometrial cancer was 2.691 (95% CI: 1.548, 4.3635, p=0.0003), or 6.383 (95% CI: 2.812, 13.68, p<0.0001) respectively, compared to the controls. The odds ratio of women who did not use IUDs developing ovarian cancer was 1.606 (95% CI: 1.057, 2.434), compared to the controls. There was no association of age at first birth and developing endometrial or ovarian cancer. Conclusion Our observational data suggested that GDM and delivery of an LGA infant are associated with an increased risk of endometrial cancer.